Interprofessional Education of Allied Health Professionals - Perspectives of Experts / Interprofessionelles Lehren und Lernen in den Gesundheitsprofessionen aus Sicht von Experten/-innen - Herinek Doreen; Wild Heike; Herzberg Jana (Sciendo, 2018)
Given increasing requirements for health care services, interprofessional cooperation between healthcare professions has been recently gaining momentum. To ensure that cooperation with other healthcare professionals does not occur for the first time in clinical settings, several projects have been developed over the past years in Germany, aiming to prepare future clinicians for interprofessional cooperation during their study or vocational training programs. The conceptual diversity underlying these projects is reflected for instance in their target groups, as well as in their different structures, contents and aims. The prevailing heterogeneity in this field partly results of structural decisions made by project designers. The present study aims to explore the perspectives of experts involved in the development of those interprofessional education programs. Accordingly, this paper aims to provide information on the perspectives of a population which has until now received little consideration in this context, and to identify and describe opportunities and challenges for the implementation of interprofessional teaching and learning processes.